Pengaruh Pemberian Alkohol Terhadap Sistem Rangka - Dewi Tri Atmaningsih (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Alcohol is an organic compound that has a hydroxyl group and consumed globally by the majority of the world's population. Alcohol consumption results in various adverse health effects, such as cirrhosis of the liver, hepatitis, cognitive and behavioral changes, and alteration of bone. Objective: To determine the effect of alcohol administration on the skeletal system of rats. Methods: Using literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results: Administration of alcohol to rats resulted various alterations of the rat’s bone. Conclusion: Excessive intake of alcohol causes bone formation alteration, less bone mineral density and bone mineral content, also increases bone loss and fracture risk.